Crystal structure, dielectric properties, and lattice vibrational characteristics of LiNiPO4 ceramics sintered at different temperatures. Issue 4 (14th December 2019) - Xiao, En‐cai; Cao, Zhikai; Li, Jianzhu; Li, Xue‐Hui; Liu, Mengting; Yue, Zhenxing; Chen, Ying; Chen, Guohua; Song, Kaixin; Zhou, Huanfu; Shi, Feng
Abstract: LiNiPO4 (LNP) ceramics were synthesized using a conventional solid‐state reaction method and different sintering temperatures. Differential scanning calorimetry (DSC), thermogravimetric (TG) analysis, and X‐ray diffraction (XRD) measurements indicated that single‐ phase olivine ( Pnma, No. 62) was formed above 750°C, and dense LNP ceramic with a theoretical density of more than 95% was obtained at 825°C. Raman and far‐infrared (IR) vibrational modes were assigned and discussed in detail. The intrinsic dielectric properties of the samples were calculated using the four‐parameter semi‐quantum (FPSQ) model based on far‐IR reflectance spectroscopy and were in good agreement with the measured values. A positive relationship existed between the Raman shift of the υ1 mode (attributed to the symmetric vibration of [PO4 ] 3− ) and the corrected permittivity, and the opposite correlation was observed between the quality factor ( Q × f ) and the damping of the υs mode as well as the distortion of the [NiO6 ] octahedra. The optimized microwave dielectric properties of the LNP ceramics sintered at 825°C include an ultralow dielectric constant (5.18) and a good quality factor (24 076 GHz, f = 17.2 GHz).